UMP introduced EAP to nurture culture of excellence among staff - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) introduced an Employee Assistance Programme (EAP) aimed at providing help and support to staff, which in turn, would transform them into a workforce that practised a culture of excellence in all aspects.